A new species and first record of Pulmoniscus Leistikow, 2001 (Isopoda, Oniscidea, Philosciidae) from Colombia - López-Orozco,Carlos Mario (2017)
Abstract A new species of Pulmoniscus Leistikow, 2001 from Department of Bolívar, Colombia, is described. It constitutes the first record of the genus for the country and for the continental portion of the Neotropics. Pulmoniscus turbanaensis n. sp. is distinguished by the male pereopod 7 ischium with concave sternal margin and the shape of the male pleopod 1. In addition, ecological remarks and a distribution map are provided.